Assessing the EC trade policy in goods - Patrick A. Messerlin (European Centre for International Political Economy (ECIPE), 2007)
The recent shift in European trade policy to negotiate bilateral agreements with no less than 24 countries is taking Europe into dangerous waters. In contrast to bilaterals envisaged by Chile, Japan, Korea, Singapore and the U.S., the bilaterals considered by the EC are characterized by high tariffs and non-tariff barriers in goods, and by restrictive regulations in services and investment. Multilateral liberalization of trade should be the centre of European trade strategy. The EC trade negotiators in industrial goods (NAMA) should aim (or should have aimed) at achieving what the European business community is asking for - namely no single industrial tariff above 15 percent. Such a target makes good economic sense. It would eliminate the tariff peaks that constitute the main obstacle faced by the European exporters, and that generate most of the protection costs imposed on the consumers in the rest of the world. Furthermore, it would increase the certainty of access to emerging markets for European exporters, and should make it easier to negotiate exceptions as simple and as predictable as possible. (...)
Keywords: 330